Bioconcentration Factor of Avicennia marina (Forsk.) and Rhizophora mucronata (Lamk.) Inhabiting Coastal Area of Semarang City on Cadmium - Hastuti, Endah Dwi; Izzati, Munifatul; Prihastanti, Erma (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2025)
Mangrove plants are expected to act as bioaccumulator for heavy metals in the coastal area. One of heavy metals with great potential risk to the environment is Cadmium (Cd). This research aimed to study the concentration of Cd in the sediment, water, and mangrove organs, as well as to analyse the bioconcentration factor of mangrove plants in the coastal area of Semarang City. This research was carried out through experimental survey. The survey was carried out to a specified environment criteria which could be considered as experiment setting, including the growing location and mangrove species. The growing location including the shore and pond area while mangrove species using Avicennia marina and Rhizophora mucronata. The parameters are Cd level in root, leaf, water and sediment. Samples of Cd was taken from leaf and root as well as water and sediment under mangrove stands growing in the shore and pond areas, then the sample was analyzed using Atomic Absorbtion Spectrophotometer (AAS) method. The data was analyzed using ANOVA and further testing using DMRT. The result suggested that Cd accumulation was much higher in the pond area, both in the water and sediment. In addition, Cd concentration in mangrove organs showed similar behaviour. Bioconcentration factor analysis suggests that A. marina and R. mucronata are potential as bioaccumulator of Cd based on BCF value more than 1, comprising the index up to 20.333 for A. marina and 24.866 for R. mucronata.